Evaluation of the Fracture Strength of Different CAD/CAM Inlay Restorations After Accelerated Aging - İşıl Karaokutan; Meryem Gülce Subaşı; Filiz Aykent; Tuba Yılmaz Savaş (Selçuk University, 2019)
Background: The purpose of this study was to compare the fracture resistance of inlay restorations manufactured by CAD/CAM using different materials after accelerated artificial aging.Methods: Class I inlay preparations were made for 40 mandibular molar teeth. The teeth were allocated into four groups (n=10) according to the type of manufacturing material used: feldspathic-ceramic (CEREC blocks); leucite-based glass-ceramic (IPS Empress CAD); resin nano-ceramic (Lava Ultimate); and a control (intact teeth). After obtaining digital impressions, restorations were designed and milled with CAD/CAM. Inlay restorations were cemented to the inlay cavities using a dual-polymerizing resin cement (Rely X Ultimate) and stored in distilled water at 37°C for a week. All the samples were then exposed to accelerated ultraviolet aging for 300 hours. Finally, a compressive load was applied to the samples until fracture. Statistical analysis was conducted using One-Way ANOVA and the Tukey HSD test (a=0.05).Results: The mean fracture strength values of the groups were; Control (1555.3±412.2 N)> Lava Ultimate (1525±394N)>IPS Empress CAD (1364.3±545.6N) > CEREC(1231.9±412.2N), respectively. However, there was no statistically significant difference in mean fracture strength among different inlay restoration groups (P>0.05). Fifty percent of the both CEREC and IPS Empress CAD groups and  60% of the Lava Ultimate group showed reparable fractures. Conclusion: The type of material used did not influence the fracture strength of inlay-restored molar teeth and inlay restorations did not weaken the strength of the restored teeth. Therefore, all of the tested materials are suitable for use in the posterior region. Keywords: Inlay, fracture strength, resin nano-ceramic, ceramic, CAD/CAM